The colombian indigenous movement´s opposition as a counterweight to power - Sánchez Montenegro, Angélica María (2015)
In order to speak of indigenous resistance and understand it in the Colombian context, wemust take into account not only the conditions of conflict but also how state power is configured. So, we should address the structural failure of the state and understand how it leads to incomplete state intervention in the whole Colombian territory, which in turn, causes unfulfillment of basic needs and lack of legitimacy in peripheral areas. Due to this failure of the state, indigenous communities native to those areas are forced to meet their needs by means of alternative routes, such as the formation of their own government, which is legitimate and legal on constitutional terms. They are able to do so with support from organizations such as the Regional Indigenous Council of the Cauca (CRIC) or the imposed link with illegal armed groups (imposed because it is not legitimate but a reality close to indigenous communities) who use their coercive force to replace public institutions and provide services such as health, safety and the maintenance of order under their particular logics.Indigenous communities have developed self-government with identity and territoriality, which leads to new forms of organization of power. An example of this is the Regional Indigenous Council of Cauca, which represents the interests of all indigenous communities of the Cauca and promotes communication with indigenous people from other areas. This work pays significant attention to the CRIC since it contains characteristics of power such as resistance, discourses of truth and a link with law.